THE EFFECT OF PROBLEM BASED FLIPPED LEARNING ON HISTORICAL CONSCIOUSNESS AND CRITICAL THINKING SKILL OF STUDENTS AT SMK NEGERI 1 DENPASAR - I Gede Juli Suwirtana Putra; I Wayan Santyasa; I Gde Wawan Sudatha (RADJA PUBLIKA, 2026)
The background of this research is the low levels of historical consciousness and critical thinking skills among students, caused by the dominance of conventional learning which tends to focus on factual memorization. This condition results in students' difficulty in connecting past events with present-day reality. This study aims to examine the effect of the Problem-Based Flipped Learning (PBFL) model on the historical consciousness and critical thinking skills of students at SMK Negeri 1 Denpasar. The method employed was a quasi-experiment with a pretest-posttest nonequivalent control group design . The research population consisted of 9 classes totaling 352 eleventh-grade students, with three classes selected through group random sampling to serve as the experimental group (PBFL), control group I ( Problem-Based Learning ), and control group II ( Direct Instruction ). Data were collected using historical consciousness questionnaires and critical thinking skills tests, then analyzed using multivariate analysis of covariance (MANCOVA) with pre-test scores as the covariates. The results indicated significant differences in both historical consciousness and critical thinking skills, simultaneously and individually, between students taught with the PBFL model compared to those taught with PBL and Direct Instruction models. Further analysis confirmed that the average scores of the PBFL group consistently outperformed the other groups. This research concludes that the implementation of the PBFL model effectively enhances students' historical consciousness and critical thinking sharpness through learning time efficiency and contextual problem-solving.